Measuring the crowd within again: a pre-registered replication study - Steegen, Sara; Dewitte, Laura; Tuerlinckx, Francis; Vanpaemel, Wolf (Frontiers in Psychology, 2014)
According to the crowd within effect, the average of two estimates from one person tends to be more accurate than a single estimate of that person. The effect implies that the well documented wisdom of the crowd effect - the crowd's average estimate tends to be more accurate than the individual estimates - can be obtained within a single individual. In this paper, we performed a high-powered, pre-registered replication study of the original experiment. Our replication results are evaluated with the traditional null hypothesis significance testing approach, as well as with effect sizes and their confidence intervals. We adopted a co-pilot approach, in the sense that all analyses were performed independently by two researchers using different analysis software. Moreover, we report Bayes factors for all tests. We successfully replicated the crowd within effect, both when the second guess was made immediately after the first guess, as well as when it was made three weeks later. The experimental protocol, the raw data, the post-processed data and the analysis code are available online.